A new species and new records of scuttle flies (Diptera: Phoridae) from Algeria - Saifi, Mounir; Disney, R. Henry L.; Doumandji, Salaheddine (Zootaxa, 2019)
Among seven species caught at wild boar carcasses in Algeria Megaselia falsum  Disney n. sp. is described and the hitherto unknown female of M. iberiensis Disney.